Penerapan Bi’ah Lughawiyah sebagai penunjang Kebahasaan di MI An Najihah Babussalam Mojorejo Kebonsari Madiun - Kuswoyo; Wiranto; Abdika Arif (El-Wasathiya: Jurnal Studi Agama, 2021)
The Arabic and English language environment or Bi'ah Lughawiyah is a Program or a madrasah agenda that has a language character, or a madrasah that has superiority in the field of Arabic and English. This Program is a container in which there are various other supporting activities, including: Language motivation (Tasyjiul Lughah), linguistic meeting (Dauroh Lughah), the linguistic Safari (Safari Lughah), Day language (Language Day), Ambassadors of Languages (Qudwah Lughah), Meet and Greet and others. These supporting activities must be carried out, and the evaluation of this Lughawiyah. So that with all the fields/activities described above, the Bi'ah Lughawiyah in the Madrasah will be created and will be preserved.